2015
DOI: 10.5194/tc-9-2429-2015
|View full text |Cite
|
Sign up to set email alerts
|

Committed retreat of Smith, Pope, and Kohler Glaciers over the next 30 years inferred by transient model calibration

Abstract: Abstract. A glacial flow model of Smith, Pope and KohlerGlaciers is calibrated by means of control methods against time varying, annually resolved observations of ice height and velocities, covering the period 2002 to 2011. The inversion -termed "transient calibration" -produces an optimal set of time-mean, spatially varying parameters together with a time-evolving state that accounts for the transient nature of observations and the model dynamics. Serving as an optimal initial condition, the estimated state f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 52 publications
5
101
0
Order By: Relevance
“…The nonuniform onset and spreading of drawdown during the altimetry era visible in our results can be used to calibrate and test numerical simulations of the ASE glaciers [Goldberg et al, 2015]. Under persistent future oceanic forcing, models indicate that thinning will expand to larger areas in the PIG and THG basins, which would contribute to accelerated ice-mass loss and associated sea-level rise [e.g., Joughin et al, 2010Joughin et al, , 2014Cornford et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonuniform onset and spreading of drawdown during the altimetry era visible in our results can be used to calibrate and test numerical simulations of the ASE glaciers [Goldberg et al, 2015]. Under persistent future oceanic forcing, models indicate that thinning will expand to larger areas in the PIG and THG basins, which would contribute to accelerated ice-mass loss and associated sea-level rise [e.g., Joughin et al, 2010Joughin et al, , 2014Cornford et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies have indicated that rates of ice discharge from this sector are expected to further grow in future, in part due to ongoing ice dynamics and in part due to projected ocean warming [Joughin et al, 2010[Joughin et al, , 2014Favier et al, 2014;Seroussi et al, 2014;Cornford et al, 2015;Goldberg et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Previous ice-flow modeling, which excluded the floating ice, suggested that these glaciers will continue to retreat even in the absence of a change in forcing (Goldberg et al, 2015). Since changes in the ASE are thought to be ocean-forced, however, understanding of processes over the floating ice and at the grounding line is key to explaining recent behavior and to any prediction of future behavior.…”
Section: Study Areamentioning
confidence: 99%
“…Similarly, Golledge et al (2008) obtained a thin, more extensive Younger Dryas ice sheet in Scotland with increased sliding. As also explained above from a theoretical perspective (mass continuity), a shallow geometry is associated with high sliding.…”
Section: Sensitivity To Sliding and Deformation Parametersmentioning
confidence: 99%
“…This time dependency has implications for other model studies of long-term dynamics of glaciers and ice caps. With growing availability of data, such studies may consider a "dynamic" or "transient" calibration (e.g., Oerlemans, 1997a;Davies et al, 2014;Goldberg et al, 2015), as opposed to a "snapshot" calibration. The "transient" method uses several sets of observations to infer model parameters, ideally at dynamically and climatically different states.…”
Section: Sensitivity To Sliding and Deformation Parametersmentioning
confidence: 99%